Дослідження і розвиток психологічних особливостей творчої соціалізації старшокласників - Сторож, О. В.; Storozh, O. V. (Волинський національний університет імені Лесі Українки, 2012)
Статтю присвячено дослідженню і розвитку психологічних особливостей творчої соціалізації старшокласників. Здійснено аналіз наукової літератури, що розкриває зміст поняття «творча соціалізація». Виявлено рівень розвитку складових соціалізації і творчого мислення старшокласників і доведено взаємозв’язок між ними. Виділено п’ять типів творчої соціалізації особистості. Проаналізовано структуру технології оптимізації творчої соціалізації старшокласників і доведено її ефективність. The article is devoted to the studying and development of psychological peculiarities of creative socialization of senior pupils. Analysis of scientific literature showing the meaning of the concept «creative socialization » has been carried out. The level of development of socialization and creative thinking components of senior pupils is revealed and interconnection between them is proved. Five types of personality’s creative socialization are outlined. The structure of the technique of optimization of creative socialization of senior pupils has been analyzed and its effectiveness has been proved.
Investigation and Development of Psychological Peculiarities of Senior Pupils’ Creative Socialization
Keywords: соціалізація; творче мислення; творча соціалізація особистості; психологічні особливості; технологія; socialization; creative thinking; creative socialization of personality; psychological peculiarities; technology